2013
DOI: 10.1519/jsc.0b013e31828909ec
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Squat Jump and Countermovement Jump From Varying Starting Positions

Abstract: The purpose of this study was to investigate the effect of 2 strategies, defined by foot placement during the initiation of the take-off on performance in vertical jumps. The additional area of interest in this experiment was whether technique of the take-off phase might be an exploratory factor that has different electromyogram (EMG) muscle activity during squat jump (SJ) and countermovement jump (CMJ) performed starting from the standard position, with parallel foot placement, and from the experimental one, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
4

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 26 publications
1
26
0
4
Order By: Relevance
“…Earlier studies found inconsistent relationships between countermovement-jump and COD performance [11,[46][47][48][49][50], varying by the tests assessed. Although electromyography (EMG) measurements have been assessed in COD [51][52][53][54] and countermovement-jumps [55,56], to the best of the authors knowledge, no earlier research has applied EMG when investigating the relationship of countermovement-jumps and COD. A high muscle peak activity is an indicator of muscular effort made during a particular action [57].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies found inconsistent relationships between countermovement-jump and COD performance [11,[46][47][48][49][50], varying by the tests assessed. Although electromyography (EMG) measurements have been assessed in COD [51][52][53][54] and countermovement-jumps [55,56], to the best of the authors knowledge, no earlier research has applied EMG when investigating the relationship of countermovement-jumps and COD. A high muscle peak activity is an indicator of muscular effort made during a particular action [57].…”
Section: Introductionmentioning
confidence: 99%
“…[25] Although jump height is determined by many other muscle groups, research has shown that the calf muscle complex accounts for an important part of the CMJ movement. [43]. …”
Section: Methodsmentioning
confidence: 99%
“…Nesta condição, menores valores de no gênero masculino corroborariam com esta maior proficiência (HAM, KNEZ & YOUNG, 2007;MACKALA et al, 2013a), uma vez que sinalizaria para um menor tempo de transição entre as fase excêntrica e concêntrica, logo maior restituição de energia elástica gerada na fase excêntrica, na fase concêntrica do passo (BOSCO, TARKKA & KOMI, 1982;BOSCO, TIHANYI, KOMI, FEKETE & APOR, 1982a;BOSCO et al, 1982b;MAULDER & CRONIN, 2005 Este cenário corrobora para a originalidade dos dados apresentados e o avanço do conhecimento de uma estratégia a fim de se estabelecer uma base teórica suficientemente forte para apoiar e justificar o uso de determinadas estratégias de execução de execução saltos ao longo de um programa em treinamento.…”
Section: P8unclassified